Hepatitis G Viral RNA in Serum and in Peripheral Blood Mononuclear Cells and Its Relation to HCV-RNA in Patients with Clotting Disorders - Sheng, Li; Soumillion, Ann; Peerlinck, Kathelijne; Verslype, Chris; Lin, Lan; Pelt, Jos van; Hess, Georg; Vermylen, Jozef; Yap, Sing Hiem (Thrombosis and Haemostasis, 1997)
The hepatitis G virus (HGV) has recently been identified as a new member of the Flaviviridae family. Infection by this virus is thought to be associated with blood borne hepatitis. In this study, the presence of HCV- and HGV-RNAs in serum or plasma (175 patients) and in peripheral blood mononuclear cells (PBMC) (133 patients) was investigated in patients with clotting disorders using a sensitive reverse transcriptase polymerase chain reaction (RT-PCR). HGV-RNA was detected in serum of 26 patients (14.8%). In apparently healthy blood donors, serum HGV-RNA was detected in 4 of 358 individuals investigated (1.12%). Ninety two percent of the 26 serum HGV-RNA positive patients had coinfection with the hepatitis C virus (HGV), especially with HCV genotype lb, the most common genotype in Belgium. Of these coinfected patients, 15 (62.5%) showed elevated serum ALT levels. Two patients who were solely infected with HGV had normal serum ALT. HGV-RNA in PBMC was found in 18 patients, of whom 3 were negative for serum HGV-RNA. As in case of HCV, HGV-RNA in PBMC is preferentially sensitive to interferon treatment. Nevertheless, rapid reappearance of HGV-RNA in PBMC was observed after cessation of treatment. In one patient, persistent serum ALT elevation seems to be associated with continued HGV viremia, despite the disappearance of serum HCV-RNA.